Comunidade de insetos predadores em hortaliças em diferentes sistemas de cultivo na região de Maringá, PR - Meira, Fernanda Maria de (2016)
Simplification of environmental structure in ecosystems for agriculture results in high losses of biodiversity, seriously reflecting on the management of agricultural pests. Due to this fact, the pursuit of environmental conservation and preservation of biodiversity has encouraged the search for more sustainable strategies in agricultural environments. This study aimed to evaluate the regional community of predatory insects in different vegetable production of agro-ecosystems. For that, beneficial insects (predators) in five farms conducted under different forms of management: 1) Organic; 2) conventional / organic transition; 3) Conventional and 4) Agroecology Urban, and the organic property and in transition, located in rural Mandaguari, PR., And conventional and urban gardens located in the urban area of Maringá, PR. Samples were collected using three different types of pitfalls: Pitfall, yellow tray (Möerick) and yellow sticky traps, with five repetitions each, totaling 15 traps in each property. Samples were collected weekly, from September 2014 to August 2015. They collected 20575 insects in total. Coleoptera was the most collected order (7239 individuals). The absolute abundance was higher in areas conventional / organic Transition (6378) and Conventional (6378). Rarefactions testified sampling efficiency in all areas. In all areas of the Shannon diversity index and Simpson were the biggest ever in Coleoptera and Dermaptera. In Organic areas, Olympic Agroecológica Urban and Urban Agroecológica grevillea trees diversity indexes were higher and Berger-Parker higher in conventional / organic transition and Conventional. Evenness did not vary greatly by order or by area. The relative abundance of the order Diptera by area showed dominance in all areas, only on Conventional Coleoptera area dominated (83%). The relative abundance of families in order in each area suggested a pattern in all experimental areas, and high percentage of a family Hymenoptera, Diptera and Hemiptera and Neuroptera.